2018
DOI: 10.3389/fimmu.2018.02463
|View full text |Cite
|
Sign up to set email alerts
|

How ERAP1 and ERAP2 Shape the Peptidomes of Disease-Associated MHC-I Proteins

Abstract: Four inflammatory diseases are strongly associated with Major Histocompatibility Complex class I (MHC-I) molecules: birdshot chorioretinopathy (HLA-A*29:02), ankylosing spondylitis (HLA-B*27), Behçet's disease (HLA-B*51), and psoriasis (HLA-C*06:02). The endoplasmic reticulum aminopeptidases (ERAP) 1 and 2 are also risk factors for these diseases. Since both enzymes are involved in the final processing steps of MHC-I ligands it is reasonable to assume that MHC-I-bound peptides play a significant pathogenetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 123 publications
(195 reference statements)
1
141
0
5
Order By: Relevance
“…Ten years later, using engineered ERAP1-ERAP2 complexes, I. Evnouchidou and colleagues verified that heterodimer formation changes enzymatic features and increases peptide-trimming efficiency, thus allowing the generation of a wider and more immunogenic antigenic repertoire [8]. Indeed, the complementary activity of the two aminopeptidases leads to the generation of a variegated antigenic repertoire, which may be altered in individuals lacking either protein [12]. Overall, it has been demonstrated that the structural changes made by ERAP1 and ERAP2 represent a key step in mature antigenic epitope generation [12].…”
Section: Biological Functions Of Erap1/2mentioning
confidence: 99%
See 4 more Smart Citations
“…Ten years later, using engineered ERAP1-ERAP2 complexes, I. Evnouchidou and colleagues verified that heterodimer formation changes enzymatic features and increases peptide-trimming efficiency, thus allowing the generation of a wider and more immunogenic antigenic repertoire [8]. Indeed, the complementary activity of the two aminopeptidases leads to the generation of a variegated antigenic repertoire, which may be altered in individuals lacking either protein [12]. Overall, it has been demonstrated that the structural changes made by ERAP1 and ERAP2 represent a key step in mature antigenic epitope generation [12].…”
Section: Biological Functions Of Erap1/2mentioning
confidence: 99%
“…Indeed, the complementary activity of the two aminopeptidases leads to the generation of a variegated antigenic repertoire, which may be altered in individuals lacking either protein [12]. Overall, it has been demonstrated that the structural changes made by ERAP1 and ERAP2 represent a key step in mature antigenic epitope generation [12].…”
Section: Biological Functions Of Erap1/2mentioning
confidence: 99%
See 3 more Smart Citations